Online Political Discourse: Exploring Differences in Effects of Civil and Uncivil Disagreement in News Website Comments. Issue 1 (2nd January 2017) - Masullo Chen, Gina; Lu, Shuning
Abstract : An experiment (N = 272) demonstrated that disagreement—either civil or uncivil—may have a chilling effect on the public discourse vital to a deliberative democracy. Both forms of disagreement—in comments posted on a news story about abortion—caused negative emotion and aggressive intentions. However, only uncivil disagreement led people to respond back uncivilly and indirectly led to greater intention to participate politically, if it aroused aggressive feelings. Findings support extending face and politeness theories to the computer-mediated space of online commenting. Results are discussed in relation to the impact on the public discourse.